Recent advances in biological and medicinal profile of schiff bases and their metal complexes: An updated version (2018–2023) - Shalu Thakur; Ankita Jaryal; Aman Bhalla (Results in Chemistry, 2024)
Schiff bases are most the widely used class of molecules in organic as well as in inorganic chemistry and are well known for fabricating stable metal complexes. Schiff bases and their metal complexes are utilized as pharmaceutically and medicinally important scaffolds because of their versatile biological profile. So herein, in this review, we summarized the recently developed biologically active Schiff bases and their metal complexes with V, Fe, Co, Ni, Cu, Zn, Zr, Rh, Pd, Cd, Sn, Ir, Pt, and Pb metals. The anti-bacterial, anti-fungal, anti-viral, anti-microbial, anti-cancer, and corrosion inhibiting studies have been compiled in the present review. Anti-bacterial activities has been described against both gram-positive (S. aureus, B. subtilis) and gram-negative (E. coli, proteus) bacteria. The anti-fungal action of various metal complexes against Candida albicans, Candida tropicalis, Candida glabrata, Aspergillusniger, and other fungal strains has been included. The in-vitro anti-viral examination and in-silico evaluation with main protease (MPro) of protein SARS-CoV-2 virus (PDB ID: 7BZ5, 7BZ5, 6LU7, 7C8U), chikungunya virus nsP4 (PDB ID: 4RY5) and HIV-1 virus (PDB ID: 6MQA) has also been summarized. Additionally, the results of cytotoxic properties against various cell lines including MCF-7, HeLa, HCT116, Dalton’s Lymphoma, SGC-7901, BGC-823, HEK-293, HEPG2, and DU-145 have been discussed. Thus ultimately, the present review highlights the recent development (2018–2023) of Schiff base metal complexes and their potency against various biological strains.